Innovation in Adding Moringa Leaf Puree (Moringa Oleifera) in the Making of Roti Jala - Elly Susanti; Miratia Afriani; Eva Amalia; Eryd Saputra (Journal Research of Social Science, Economics, and Management, 2025)
Concerns over the adverse effects of using synthetic dyes in food products—such as the risk of allergies and long-term health issues—have prompted the need for safer and more nutritious natural dye alternatives. This research aims to explore the innovation in adding Moringa Leaf Puree (Moringa Oleifera) in the making of Roti Jala as an effort to present traditional foods that are healthier and more functional. The research employed an experimental approach with three treatments, namely the addition of Moringa leaf puree at levels of 25%, 50%, and 75% of the total wheat flour. The results showed that the 25% Moringa leaf treatment was the most preferred formulation among the panelists, achieving an overall preference rate of 81%, especially in terms of color, texture, and taste. The ANOVA test indicated significant differences in color, aroma, and taste, but not in texture. Macronutrient content analysis revealed an increase in energy, protein, and fat corresponding with the higher addition of Moringa leaf puree, where the 75% sample yielded 872.2 kcal of energy, 210.7 g of protein, and 179.2 g of fat per 200 grams serving. This study demonstrates that Moringa leaf puree can serve as a natural coloring agent while enhancing nutritional value without diminishing the typical characteristics of Roti Jala. These findings are expected to contribute to the development of traditional culinary innovations that are healthy, economically valuable, and supportive of sustainable food product advancement.